Growth Mindset Pedagogy in Inclusive Classroom - Sharma, Anjali; Singh, Sukanya (Voices of Teachers and Teacher Educators, 2022)
The study themed to explore the growth mindset theory from the pedagogical perspective and its viability for inclusion in the classroom. To reach the theme, the study focused on three questions: What are the growth mindset pedagogical practices? How do these practices assist in creating a growth mindset classroom culture? What kind of attitude develops among learners? A qualitative approach was employed to fulfill these concerns.A field survey in an inclusive school was undertaken, and data was collected using observation and interview schedules on 30 participants. The study identified various growth mindset pedagogical practices and found that those practices assist in creating a growth mindset classroom culture and develop the growth mindset of the teachers and learners, which leads to the attitude among the learners to push them for learning in all circumstances. It is recognised from the growth mindset theory,which produces a specific pedagogical practice mentioned in the analysis part of the paper, named growth mindset pedagogy,that is viable for inclusion in the classroom.